Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The question I am working on: Evaluate

$$\frac{1}{2} \int^1_0{x^4 (1-x)^4 } dx \le \int^1_0{\frac{x^4 (1-x)^4}{1+x^2}} dx \le \int^1_0{x^4 (1-x)^4 } dx$$

So using integration by parts to solve:

(letting $u=(1-x)^4$ and $dv=x^4$)

$$\int{x^4 (1-x)^ 4} dx = \frac{4}{5}x^5(x-1) - \frac{4}{5}\left(\frac{x^7}{7} - \frac{x^6}{6}\right)+c$$

Is it correct so far? If so ...

$$\int^1_0{ x^4 (1-x)^4 } dx = \frac{4}{5}\left(\frac{1}{6}-\frac{1}{7}\right)=\frac2{105}$$

$$\frac{1}{2} \int^1_0{ x^4 (1-x)^4 } dx = \frac{2}{5}\left(\frac{1}{6}-\frac{1}{7}\right)=\frac1{105}$$

But

$$\int\frac{{x^4(1-x)^4}}{1+x^2} dx = ??$$


Since I found $\int{{x^4(1-x)^4}} dx$. I thought of integration by parts, letting $u=\frac{1}{1+x^2}$, $dv = x^4(1-x)^4$. But I will get a very complicated $v$ to integrate later? Same if I did it the other way around?

share|improve this question
    
What do you mean by evaluating the inequality? It is certainly true since $1\le1+x^2\le2$ on $[0,1]$. Do you really need the central integral? If so, note that $$\frac{x^4(1-x)^4}{1+x^2}=x^4(x-1)^2\left(1-\frac{2x}{1+x^2}\right)$$ while you can use $\int\frac{2x}{1+x^2}=\ln(1+x^2)+c$ and $\int\frac{1}{1+x^2}=\arctan(x)+c$ to integrate the linear and constant remainder terms from the general polynomial quotient. –  bgins Apr 9 '12 at 12:11
    
(Sort of) related: math.stackexchange.com/questions/1956/… –  Hans Lundmark Apr 9 '12 at 14:21
add comment

2 Answers

up vote 6 down vote accepted

Using the binomial theorem and then long division, $$ \frac{x^4(1-x)^4}{1+x^2}= \frac{x^4(x^4-4x^3+6x^2-4x+1)}{1+x^2}= x^6-4x^5+5x^4-4x^2+4-\frac{4}{1+x^2} $$ so that $$ \int_0^1 \frac{x^4(1-x)^4}{1+x^2}dx= \frac17-\frac46+\frac55-\frac43+\frac41-4\arctan\frac\pi4 =\frac{22}7-\pi\approx\frac1{790.~833~125~927~563} $$ There's also a problem with your integration by parts since $$ \eqalign{ u &=& (1-x)^4=(x-1)^4 &\qquad& v &=& x^4 \\\\ du &=& 4(x-1)^3 \, dx &\qquad& dv &=& \frac15 x^5 dx } $$ so $$ \eqalign{ I_1 &= \int_0^1 x^4 (1-x)^4 dx \\ &= \int u\,dv = uv - \int v\,du \\ &= \left[ \frac45 x^5 (1-x)^4 \right]_0^1 + \frac45 \int_0^1 x^5 (1-x)^3 dx \\ &= \frac45 \int_0^1 x^5 (1-x)^3 dx \\ &= \frac45\cdot\frac36 \int_0^1 x^6 (1-x)^2 dx \\ &= \frac45\cdot\frac36\cdot\frac27 \int_0^1 x^7 (1-x) dx \\ &= \frac45\cdot\frac36\cdot\frac27\cdot\frac18 \int_0^1 x^8 dx \\ &= \frac45\cdot\frac36\cdot\frac27\cdot\frac18\cdot\frac19 = \frac1{630} } $$ where we had to apply integration by parts repeatedly using $$u=(1-x)^n,~dv=x^m\,dx$$ $$du=-n(1-x)^{n-1}\,dx,~v=\frac{x^{m+1}}{m+1}\implies$$ $$\int x^m(1-x)^ndx=\frac{x^n(1-x)^{m+1}}{m+1} +\frac{n}{m+1}\int x^{m+1}(1-x)^{n-1}dx$$ until the powers of $(1-x)$ went away. In fact, we just made a special case of the calculation $$ \int_0^1 x^a (1-x)^b = B(a+1,b+1) = \frac{a!~b!}{(a+b+1)!} $$ of the well-known Beta function for $a=b=4$ (our method works for $a,b\in\mathbb{N}$ and, with an adaptation of the above formula using the Gamma function, also for real $a,b\ge0$).

Now we can see that the reciprocal of the central integral is certainly beween $630$ and $1260$.

share|improve this answer
    
@TMM, thanks, I fixed it. –  bgins Apr 9 '12 at 13:21
    
$du=-4(x-1)^3$. –  David Mitra Apr 9 '12 at 13:23
1  
@DavidMitra: Actually I had $du$ right but used it incorrectly, which is what you surely noticed. For the general step, $$u=(1-x)^n,~dv=x^m\,dx$$ $$du=-n(1-x)^{n-1}\,dx,~v=\frac{x^{m+1}}{m+1}\implies$$ $$\int x^m(1-x)^ndx=\frac{x^n(1-x)^{m+1}}{m+1}+\frac{n}{m+1}\int x^{m+1}(1-x)^{n-1}dx$$ –  bgins Apr 9 '12 at 13:44
add comment

Hint :

Rewrite integral into form :

$$I=\int \frac{x^8+x^6}{1+x^2} \,dx + \int \frac{x^6+x^4}{1+x^2} \,dx +4\cdot \int \frac{x^6}{1+x^2} \,dx -4\cdot \int \frac{x^7+x^5}{1+x^2} \,dx$$

for third integral do long division .

share|improve this answer
1  
Ah, I see the light at last... I think it might help if you explained first (for us mere mortals) that $$\eqalign{(1-x)^4&=x^4-4x^3+6x^2-4x+1\\&=(x^2+1-4x)(1+x^2)+4x^2}$$ $$\frac{(1-x)^4}{1+x^2}=x^2+1-4x+4\frac{x^2}{1+x^2}$$ $$\frac{x^4(1-x)^4}{1+x^2}=x^6+x^4-4x^5+4\frac{x^6}{1+x^2}$$ $$\frac{x^4(1-x)^4}{1+x^2}=\frac{x^8+x^6}{1+x^2}+\frac{x^6+x^4}{1+x^2}-4\frac{x^‌​7+x^5}{1+x^2}+4\frac{x^6}{1+x^2}$$ –  bgins Apr 9 '12 at 23:37
1  
@bgins Do you have a proof that you are mortal or it is just your hypothesis.... –  pedja Apr 10 '12 at 9:10
    
@pedja, LOL. Can I say its a fact? –  Jiew Meng Apr 10 '12 at 12:25
    
@pedja: I'm married (QED), which implicitly constitutes not only a constructive proof of my mortality, but comes also with canonical induced lift and pair of projections which alas don't commute. –  bgins Apr 10 '12 at 13:34
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.